BRANDING AND DIGITAL PROMOTION STRATEGIES OF STREET COFFEE MSMES TO ENHANCE SALES COMPETITIVENESS: A CASE STUDY IN KOTABUMI, INDONESIA - Muhamad Ilham; Irsandi (PT. Jurnal Center Indonesia Publisher, 2026)
The rapid growth of Indonesia’s coffee industry has intensified competition among micro, small, and medium enterprises (MSMEs), particularly street coffee businesses that rely on simple concepts, affordability, and accessibility. This study aims to analyze branding and digital promotion strategies implemented by street coffee MSMEs in Kotabumi, North Lampung, to enhance sales competitiveness. A qualitative case study approach was employed. Data were collected through in-depth interviews with business owners and employees, direct observation, and documentation of digital promotional activities on social media platforms. Data were analyzed using the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing. The findings reveal that branding strategies were implemented through brand identity development, including business name, logo, color consistency, booth design, and product differentiation. Digital promotion strategies mainly utilized Instagram, TikTok, and WhatsApp Business through product photos, coffee-making videos, and promotional content. These strategies positively impacted market reach, customer acquisition, and sales stability. However, several constraints were identified, such as limited resources, inconsistent visual identity, and suboptimal content management. This study concludes that consistent branding and planned digital promotion are essential to strengthening competitiveness and ensuring the sustainability of street coffee MSMEs.